Study the Factors that Affect the Work Performance of Employees in the North Region Power System Management Department - Philaboun, Salongsay; Kounlaxay , Kalaphath; Orphomma , Sounith (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The objective of this study was to examine the levels of work motivation among employees in the north region power system management department. The study employed a quantitative research methodology, utilizing a questionnaire to survey the opinions of 308 employees. The research instrument featured a 5-point Likert scale. The statistical methods used for data analysis included frequency, percentage, mean , and standard deviation (S.D). The results of the study revealed that the overall level of work motivation among employees in the north region power system management department was at a high level, with a mean score of 4.16. Regarding the performance of the employees, it was found that motivation factors were at the highest level, consisting of five aspects ranked by their mean scores from highest to lowest: 1) Job security; 2) Work responsibility and achievement; 3) Nature of work; 4) Recognition and respect; and 5) Career advancement, respectively. Furthermore, the level of hygiene factors (maintenance factors) was at a high level, comprising six aspects ranked by mean scores from highest to lowest: 1) Relationships with supervisors and colleagues; 2) Salary; 3) Policy and administration; 4) Supervision and management methods; 5) Welfare; and 6) Working environment, respectively.